Studying the impact of the organizational commitment on the job performance - Mojtaba Rafiei; Mohammad Taghi Amini; Navid Foroozandeh (Management Science Letters)
Success of any organization depends on the performance of its employees. Enhancing organizational commitment among employees is an important aspect to perform better. The purpose of this study is to examine the effect of three components of organizational commitment; namely Affective, Continuance and Normative commitment, on employee’s performance. The study is applied among 244 employees of Cooperatives, Labor and Social Welfare department of Markazi Province using a single-stage cluster sampling. The study uses a standard questionnaire for organizational commitment developed by Allen and Meyer and job performance questionnaire developed by Patterson were used to gather data. Structural equations modeling (SEM) technique has been used for data analysis. The result of this analysis indicates that the organizational commitment had a positive significant effect on the job performance. In addition, the study also showed that all three dimensions of organizational commitment, Affective, continuance, and normative commitment, had a positive significant effect on the job performance. From the findings, it has been proved that job performance was strongly associated with employee's commitment.